Пчелы: Повесть о биологии пчелиной семьи и победах науки о пчелах / Е. Н. Васильева - Васильева Е. Н. (Эврика, 1981)
Экземпляры: б/ф-12 (20110419) / Инвентарный номер: 2191 / Цена: 0.70 / Авт.знак: В 19 / ББК: 46.9